2002
DOI: 10.1051/lait:2002034
|View full text |Cite
|
Sign up to set email alerts
|

Ibores goat's milk cheese: Microbiological and physicochemical changes throughout ripening

Abstract: -The microflora of Ibores cheese made with raw goat's milk without any starter addition was studied throughout the ripening period. The microbial counts for total lactic acid bacteria, presumptive lactococci and presumptive lactobacilli attained maxima of 9-10 log units with little or no variation throughout ripening. Leuconostocs and enterococci levels were 2-3 log units lower, also with little variation. Coliforms and staphylococci declined steadily from relatively high initial counts, the coliforms to low l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
1
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
(41 reference statements)
6
26
1
9
Order By: Relevance
“…In the last decade, they have been detected (COGAN et al, 1997;MAS et al, 2002; PSONI; TZANETAKIS; LITOPOULOUdecreased slightly (p > 0.05) reaching, in 30-day old cheeses, similar levels to those found in milk; these values were much lower than those reported previously (PEREIRA; VASEK; FUSCO, 1995;VASEK et al, 2004VASEK et al, , 2008 for artisanal cheeses at the sales points in Corrientes. Numerous authors reported higher levels (ZÁRATE et al, 1997;ESTEPAR et al, 1999;GARCÍA FONTÁN et al, 2001;MENÉNDEZ et al, 2001; PSONI; TZANETAKIS; LITOPOULOU-TZANETAKI, 2003; VOLKEN DE SOUZA; DALLA ROSA; ZACHIA AYUB, 2003) for starter-free cheeses made from raw milk at the same ripening time.…”
Section: Microbial Population Dynamicsmentioning
confidence: 66%
See 1 more Smart Citation
“…In the last decade, they have been detected (COGAN et al, 1997;MAS et al, 2002; PSONI; TZANETAKIS; LITOPOULOUdecreased slightly (p > 0.05) reaching, in 30-day old cheeses, similar levels to those found in milk; these values were much lower than those reported previously (PEREIRA; VASEK; FUSCO, 1995;VASEK et al, 2004VASEK et al, , 2008 for artisanal cheeses at the sales points in Corrientes. Numerous authors reported higher levels (ZÁRATE et al, 1997;ESTEPAR et al, 1999;GARCÍA FONTÁN et al, 2001;MENÉNDEZ et al, 2001; PSONI; TZANETAKIS; LITOPOULOU-TZANETAKI, 2003; VOLKEN DE SOUZA; DALLA ROSA; ZACHIA AYUB, 2003) for starter-free cheeses made from raw milk at the same ripening time.…”
Section: Microbial Population Dynamicsmentioning
confidence: 66%
“…Some authors (BERESFORD et al, 2001;WOUTERS et al, 2002;PELÁEZ;REQUENA, 2005) reported the predominance of Lactococcus strains in a great variety of cheeses. Other authors (COGAN et al, 1997;ZÁRATE et al, 1997;ESTEPAR et al, 1999;MAS et al, 2002;PESIC-MIKULEC;JOVANOVIC, 2005) reported their preponderance in cheeses made from raw milk and spontaneous fermentation up to 1 month of ripening.…”
Section: Microbial Population Dynamicsmentioning
confidence: 99%
“…Borelli (2006) also found this species in artisanal Minas cheese produced in the Serra da Canastra region. In studies of the microbial diversity of artisanal cheeses from Spain (Mas et al, 2002) and Greece (Gerasi, Litopoulou-Tzanetaki, & Tzanetakis, 2003), W. paramesenteroides was also found. Ferreira and co-workers isolated W. paramesenteroides from Marajó cheese in the State of Pará, Brazil (Ferreira, Seixas, Eller, Nero, & Carvalho, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…None of these cheeses come from the Andalusian region. Although there are studies of goat cheese characteristics in Camerano cheese (Gonzalez-Fandos et al 2000), in Ibores cheese (Mas et al 2002), in Majorero cheese (Alvarez et al 2007;Fresno and Alvarez 2012;Sanchez-Macias et al 2010), in Murcia al Vino cheese , in Palmero cheese (Fresno et al 2011), and in Tenerife cheese (Peláez Puerto et al 2004), reports on traditional Andalusian cheeses have been sparse or not updating (Fernández-Salguero and Gómez Díaz 1997) or examining their nutritional aspects (Moreno-Rojas et al 2010). To the best of our knowledge, no recent studies have reported the effect of the breed, ripening time, rennet type, or heat treatment on the physicochemical properties of Andalusian artisanal goat's milk cheese.…”
Section: Introductionmentioning
confidence: 99%